Analisis Penyebab Kesulitan Belajar pada Implementasi Kurikulum Merdeka: Studi Kasus pada Usia 13-15 Tahun Siswa SMP - Anisa Sri Apriliani; Raihana Mutiara Putri; Sitti Chadidjah (Pusat Penelitian dan Pengabdian kepada Masyarakat Sekolah Tinggi Agama Islam Nahdlatul Wathan Samawa Sumbawa Besar, 2025)
This article discusses an analysis of the causes of learning difficulties related to the implementation of the Independent Curriculum in case studies aged 13-15 years/junior high school students. The Merdeka Curriculum, which is implemented in Indonesia, aims to enable students to deepen adequate concepts and skills using a variety of intracurricular learning. However, its implementation still faces various challenges, one of which is learning difficulties, especially those experienced by junior high school students. This article examines how to analyze the causes of learning difficulties in the implementation of the Merdeka curriculum. Apart from that, this article also provides an explanation of the causes of learning difficulties experienced by junior high school students during the implementation of the Merdeka curriculum. Through this approach, it is hoped that it can overcome and also prevent other causes of learning difficulties, which may occur in junior high school students during the implementation of the Merdeka curriculum.